2020
DOI: 10.1159/000511045
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis Suppurativa: Proposal of Classification in Two Endotypes with Two-Step Cluster Analysis

Abstract: <b><i>Introduction:</i></b> Hidradenitis suppurativa (HS) is a chronic, inflammatory, recurrent disorder of the pilosebaceous unit. Currently, several attempts have been made to classify this disease according to its pathogenesis and clinical manifestations. We attempted at classifying 103 patients using two-step cluster analysis. <b><i>Methods:</i></b> The final model included body mass index, C-reactive protein (CRP), and serum concentrations of IL-1, IL-6, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
(44 reference statements)
1
19
0
Order By: Relevance
“…We have previously reported that LC2 phenotype (corresponding to C1 endotype) is more frequent in our geographical area (Mediterranean region) than LC1 and LC3 phenotypes, and it could have provoked an inclusion bias. 10 Also, the fact that inflammatory nodules and abscesses account for a lower score in the IHS4 scale compared with sinus tracts and Hurley staging (lesions are usually non confluent) may give the impression that patients treated with dapsone in this series have a less severe HS. The fact that dapsone was not equally effective in patients with sinus tracts probably accounts for a worse response of LC1 phenotype, comprising patients with higher body mass index and inflammatory load, who respond better to more powerful…”
Section: Discussionmentioning
confidence: 84%
“…We have previously reported that LC2 phenotype (corresponding to C1 endotype) is more frequent in our geographical area (Mediterranean region) than LC1 and LC3 phenotypes, and it could have provoked an inclusion bias. 10 Also, the fact that inflammatory nodules and abscesses account for a lower score in the IHS4 scale compared with sinus tracts and Hurley staging (lesions are usually non confluent) may give the impression that patients treated with dapsone in this series have a less severe HS. The fact that dapsone was not equally effective in patients with sinus tracts probably accounts for a worse response of LC1 phenotype, comprising patients with higher body mass index and inflammatory load, who respond better to more powerful…”
Section: Discussionmentioning
confidence: 84%
“…5 Whether better responses can be achieved with a particular cytokine inhibitor in a concrete phenotype or endotype has not been studied so far. 5…”
Section: Treatmentmentioning
confidence: 99%
“…Also, clinically distinguished phenotypes have been shown to have different cytokine profiles, and thus would probably correspond to endotypes. 5 Whether better responses can be achieved with a particular cytokine inhibitor in a concrete phenotype or endotype has not been studied so far. 5 Furthermore, differences have been found between cytokine profiles in fistula drainage.…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations